Penggunaan aplikasi Tik Tok sebagai Media Pembelajaran SKI pada Masa Pandemi Covid-19 di MI Miftahussudur 01 Dagangan - Syaibani, Izatul A'yun; Zainiyati, Husniyatus Salamah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
The pandemic COVID-19 has changed conditions in the world of education. Face to face leraning becomes online leraning. This is a new challenge for teachers to be more creative in using media when teaching, especially in boring lessons for students such as SKI. Tik Tok is one of the media used in SKI learning at MI Miftahussudur because this application has many features that are very supportive when used as a learning medium, besides Tik Tok is currently a famaous application, so it can attract student’s attention and enthusiasm. This research aims to know effectiveness of using learning by Tik Tok media in SKI lessons during the pandemic. This research use qualitative research and data collection techniques through interviews, observation, and documentation. The results of this research show that the use of Tik Tok in SKI learning at MI Miftahussudur during the pandemic covid-19 is quite effective. Because students are more enthusiastic in learning and the material presented by the teacher can be understood well. Key word : Tik Tok; SKI Learning; Covid-19